2009
DOI: 10.2106/jbjs.h.00703
|View full text |Cite
|
Sign up to set email alerts
|

Refrigerated Osteoarticular Allografts to Treat Articular Cartilage Defects of the Femoral Condyles

Abstract: Transplantation of refrigerated osteoarticular allografts stored between fifteen and twenty-eight days provides significant functional and clinical improvement after an average follow-up of three years in patients treated for a full-thickness osteochondral defect of the femoral condyle, with similar outcomes to historical reports of patients with fresh allograft implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
142
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(149 citation statements)
references
References 25 publications
2
142
0
1
Order By: Relevance
“…The biochemical composition and structural properties of the grafts were not adversely affected by the storage time. Furthermore, LaPrade et al [18] correlated chondrocyte viability with outcomes by showing functional and clinical improvements in patients with symptomatic osteochondral defects after transplantation of allografts stored up to 28 days. These findings suggest implantation of viable chondrocytes by the critical 28-day mark is essential to maintenance of the integrity of the extracellular cartilaginous matrix, preservation of the physiologic and biochemical properties of the graft, and ultimate graft survival with time.…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical composition and structural properties of the grafts were not adversely affected by the storage time. Furthermore, LaPrade et al [18] correlated chondrocyte viability with outcomes by showing functional and clinical improvements in patients with symptomatic osteochondral defects after transplantation of allografts stored up to 28 days. These findings suggest implantation of viable chondrocytes by the critical 28-day mark is essential to maintenance of the integrity of the extracellular cartilaginous matrix, preservation of the physiologic and biochemical properties of the graft, and ultimate graft survival with time.…”
Section: Discussionmentioning
confidence: 99%
“…Freezing the joint cartilage leads to chondrocyte cell death and decreases the histological and biomechanical properties of the matrix (14)(15)(16) . Possible causes of incapacity to survive freezing include the small penetration of cryopreservation solutions in the tissue, different freezing speeds of the various layers of the matrix, and the high water content in the extracellular matrix.…”
Section: Basic Sciencementioning
confidence: 99%
“…A 96% survival rate was shown by McCulloch et al (18) in a study of 25 consecutive patients treated for lesions of the femoral condyle, with minimum follow-up of two years. LaPrade et al (15) showed good clinical results for the FOAT stored for between 15 and 28 days after procurement, with a mean follow-up time of three years.…”
Section: Clinical Evidencementioning
confidence: 99%
“…Osteochondral allografting is one of the options for treating large cartilage defects secondary to osteonecrosis, osteochondritis dissecans, or traumatic injury [7,9,10,23]. Although the use of fresh osteochondral allografts initially was limited to a small number of institutions in North America, in 1998, commercial cold-stored osteochondral allografts became available for public use [10].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike traditional fresh allografts, cold-stored specimens are maintained in a hypothermic nutritive medium and must undergo a 14-day sterility testing protocol for donor bacteria and viruses [18]. Currently, improvements of outcomes and function after transplantation of osteochondral allografts stored from 15 to 48 days for treating cartilage defects of the knee have been reported during an average followup of 3 to 4 years [9,23]. As articular cartilage matrix in grafted tissues is dependent on chondrocyte metabolism for long-term maintenance, metabolically viable chondrocytes are critical for the functional survival of allografts [6,18].…”
Section: Introductionmentioning
confidence: 99%